More lesson plans for substitute teachers : classroom-tested activities from the National Council of Teachers of English. - National Council of Teachers of English (Urbana, Ill. : National Council of Teachers of English, 2002)
Contains twenty-five lesson plans for use in middle and high school classrooms that require little advance preparation, covering public speaking, language exploration and vocabulary, writing, and poetry.
Includes bibliographical references.
Professional
Keywords: English language -- Study and teaching (Secondary); Language arts (Secondary); Lesson planning; Substitute teachers; English language -- Study and teaching; Language arts; Lesson planning; Substitute teachers